Mindful Learning dalam Pembelajaran Pendidikan Agama Islam: Strategi Meningkatkan Keterlibatan Emosional dan Psikomotorik Gen Z - Nata, Balqisa Ratu; Soraya, Irma; Kurjum, Mohammad (IAIN Pontianak, 2025)
Generation Z students show challenges in emotional and psychomotor engagement in Islamic Religious Education (PAI) learning due to high digital distractions and low reflection of spiritual values. Mindful learning, which emphasizes full awareness in the learning process, is offered as a pedagogical strategy to overcome these problems. This study aims to analyze the application of mindful learning in increasing the emotional and psychomotor engagement of Gen Z in PAI learning. The method used is a literature study based on descriptive qualitative analysis of the theory and practice of mindful learning in the context of PAI material. The results of the study show that in the material on Etiquette in Using Social Media, mindful learning is effective in fostering ethical awareness through reflection of students' digital experiences. Meanwhile, in the material on Marriage in Islam, simulation activities and creative projects are able to generate meaningful psychomotor engagement. In conclusion, mindful learning is able to unite the cognitive, affective, and psychomotor dimensions in an integrated manner in PAI learning. The implications of this study lead to the need for teacher training in mindfulness strategies, development of reflection-based curriculum, and creation of learning spaces that support psychological safety and contextual spiritual practices. This approach opens up opportunities for a more relevant and in-depth transformation of religious education for today's digital generation.